Newcastle Writings 1977 - Robert Self Gallery, Newcastle; Spectro Arts Workshop, Newcastle; Art & Language; Atkinson, Conrad; Bunting, Basil; Burgin, Victor; Davies, Peter; Hilliard, John; Stezaker, John; Tagg, John (Newcastle : Northern Arts Gallery, 1977)
The Newcastle Writings derive from an extraordinary event in recent exhibition history, when the artists contributing to this volume exhibited concurrently in galleries and public spaces throughout Newcastle-upon-Tyne, during October and November, 1977
Newcastle Writings 1977: Three Newcastle galleries were responsible for organising the exhibition: Robert Self Gallery, Spectro Arts Workshop and Northern Arts Gallery, Newcastle. This book is published in association with the exhibition.
Engels
kunstcatalogus
Keywords: Newcastle